Mini cows but maxi milk - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Mini-cows produce more meat and milk per hectare than normal sized animals. This is the claim of a Mexican veterinarian who, over the last 17 years, has bred Brahman cattle to be smaller rather than larger. Dr Jose Berruecos, Director of the...